Evaluation of the PCI method for coffee sustainability in the Peca district, Bagua Capital 2022 - Santamaría Baldera, Nemesio (2023)
The economic sustainability of coffee producers in the Amazon Region has been at the center of the debate during the last years, this has always been the problem in the agricultural system; therefore, the objective of the research was to describe the importance of the PCI method for the sustainability of coffee in the district of La Peca, Bagua. The type of research is descriptive, basic and non-experimental design, in order to characterize the phenomenon, using the quantitative approach, with a population of 140 farmers, in which a non-probabilistic sampling was taken with a sample of 60 coffee growers, for the application of the questionnaire. The application of the PCI method generates a great contribution in the selection of indicators for the analysis of the sustainability of coffee production, obtaining 7 indicators of the social dimension, 8 indicators of the economic dimension and 7 indicators for the environmental dimension. The PCI method generates a great impact because it facilitates the analysis of a set of variables and attributes in the identification of a group of indicators used for the analysis of the sustainability of coffee production in the La Peca district.